Cost-effectiveness analysis of HLA-B*58: 01 genetic testing before initiation of allopurinol therapy to prevent allopurinol-induced Stevens-Johnson syndrome/toxic epidermal necrolysis in a Malaysian population - Chong, Huey Yi; Lim, Yi Heng; Prawjaeng, Juthamas; Tassaneeyakul, Wichittra; Mohamed, Zahurin; Chaiyakunapruk, Nathorn (Lippincott, Williams & Wilkins, 2017)
Objective Studies found a strong association between allopurinol-induced Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) and the HLA-B∗58:01 allele. HLA-B∗58:01 screening-guided therapy may mitigate the risk of allopurinol-induced SJS/TEN. This study aimed to evaluate the cost-effectiveness of HLA-B∗58:01 screening before allopurinol therapy initiation compared with the current practice of no screening for Malaysian patients with chronic gout in whom a hypouricemic agent is indicated. Methods This cost-effectiveness analysis adopted a societal perspective with a lifetime horizon. A decision tree model coupled with Markov models were developed to estimate the costs and outcomes, represented by quality-adjusted life years (QALYs) gained, of three treatment strategies: (a) current practice (allopurinol initiation without HLA-B∗58:01 screening); (b) HLA-B∗58:01 screening before allopurinol initiation; and (c) alternative treatment (probenecid) without HLA-B∗58:01 screening. The model was populated with data from literature review, meta-analysis, and published government documents. Cost values were adjusted for the year 2016, with costs and health outcomes discounted at 3% per annum. A series of sensitivity analysis including probabilistic sensitivity analysis were carried out to determine the robustness of the findings. Results Both HLA-B∗58:01 screening and probenecid prescribing were dominated by current practice. Compared with current practice, HLA-B∗58:01 screening resulted in 0.252 QALYs loss per patient at an additional cost of USD 322, whereas probenecid prescribing resulted in 1.928 QALYs loss per patient at an additional cost of USD 2203. One SJS/TEN case would be avoided for every 556 patients screened. At the cost-effectiveness threshold of USD 8695 per QALY, the probability of current practice being the best choice is 99.9%, in contrast with 0.1 and 0% in HLA-B∗58:01 screening and probenecid prescribing, respectively. This is because of the low incidence of allopurinol-induced SJS/TEN in Malaysia and the lower efficacy of probenecid compared with allopurinol in gout control. Conclusion This analysis showed that HLA-B∗58:01 genetic testing before allopurinol initiation is unlikely to be a cost-effective intervention in Malaysia.